The effect of two selective A(1)‐receptor agonists and the bitopic ligand VCP746 on heart rate and regional vascular conductance in conscious rats - Cooper, Samantha L. (Br J Pharmacol, 2020)
BACKGROUND AND PURPOSE: Adenosine is a local mediator that regulates physiological and pathological processes via activation of four GPCRs (A(1), A(2A), A(2B), and A(3)). We have investigated the effect of two A(1)‐receptor‐selective agonists and the novel A(1)‐receptor bitopic ligand VCP746 on the rat cardiovascular system. EXPERIMENTAL APPROACH: The regional haemodynamic responses of these agonist was investigated in conscious rats. Male Sprague–Dawley rats (350–450 g) were chronically implanted with pulsed Doppler flow probes on the renal, mesenteric arteries and the descending abdominal aorta and the jugular vein and caudal artery catheterized. Cardiovascular responses were measured following intravenous infusion (3 min each dose) of CCPA (120, 400, and 1,200 ng·kg(−1)·min(−1)), capadenoson or adenosine (30, 100, and 300 μg·kg(−1)·min(−1)), or VCP746 (6, 20, and 60 μg·kg(−1)·min(−1)) following pre‐dosing with DPCPX (0.1 mg·kg(−1), i.v.) or vehicle. KEY RESULTS: CCPA produced a significant A(1)‐receptor‐mediated decrease in heart rate that was accompanied by vasoconstrictions in the renal and mesenteric vascular beds but an increase in hindquarters vascular conductance. The partial agonist capadenoson also produced an A(1)‐receptor‐mediated bradycardia. In contrast, VCP746 produced increases in heart rate and renal and mesenteric vascular conductance that were not mediated by A(1)‐receptors. In vitro studies confirmed that VCP746 had potent agonist activity at both A(2A)‐ and A(2B)‐receptors. CONCLUSIONS AND IMPLICATIONS: These results suggest VCP746 mediates its cardiovascular effects via activation of A(2) rather than A(1) adenosine receptors. This has implications for the design of future bitopic ligands that incorporate A(1) allosteric ligand moieties.